The Role of Hadith in Building Family Resilience Against the Threat of Abuse - Almaajid, Rizqi (Yayasan Albahriah Jamiah Indonesia, 2025)
Family resilience is a fundamental aspect of Islamic teachings, which view the family not only as a biological unit but also as a spiritual institution responsible for shaping morally strong individuals. However, in recent years, sexual abuse has increasingly threatened the integrity of families, even in environments that should be the safest. This study aims to explore the role of hadith as a source of values in preventing abuse and strengthening family resilience. Employing a qualitative descriptive approach with library research methods, this study analyzes classical and contemporary Islamic literature, particularly hadiths concerning family ethics, child protection, and social morality. The results indicate that hadiths offer ethical guidance for building harmonious family relationships, emphasizing compassion, respect, and responsibility. Prophet Muhammad SAW’s exemplary conduct towards his family is a model for parents in nurturing children’s character. Furthermore, the study highlights the importance of implementing prophetic values in family education as a preventive measure against sexual abuse. Hadiths not only prohibit harm and promote respectful interaction but also teach parents to be active educators and protectors. In conclusion, hadiths serve as a moral framework that can fortify families against the challenges of modern society, especially moral degradation. Strengthening family resilience based on hadith is thus a strategic religious effort to build a safe, respectful, and dignified society.